ANALISIS KEPATUHAN PELAKSANAAN PEMOTONGAN PAJAK PENGHASILAN PASAL 15 DI PT PELABUHAN INDONESIA (PERSERO) REGIONAL 4 BITUNG - Astried Monica Limahelu; Dhullo Afandi; Wulan Kindangen (Universitas Sam Ratulangi, 2023)
PT Pelabuhan Indonesia (Persero) Regional 4 Bitung from January to April 2022 uses ships owned by PT Herlin Samudera Line so that Article 15 income tax is cut. This study aims to determine the compliance of the implementation of Article 15 Income Tax withholding at PT Pelabuhan Indonesia (Persero) Regional 4 Bitung in accordance with applicable tax regulations. This study used a type of qualitative descriptive research. The method of data collection in this study is through interviews, and documentation. The results showed that PT Pelabuhan Indonesia (Persero) Regional 4 Bitung has complied materially because it has been correct in calculating Article 15 Income Tax and is correct in deducting Article 15 Income Tax. But it did not comply formally because there was a delay in depositing Article 15 income tax for the March tax period.